Online assessment system for primary school - Athirah Nur Syaza, Sarbani (2018)
Assessment system is a method or tools that are used by the educator to evaluate student performance in learning. Through the exam-oriented assessment system, the student’s exam evaluation will be recorded. The educator will know the performance of the student based on the recorded assessment. With Online Assessment System, the educator can input the assessment validate into database and also view student info and also their performance throughout the year of the school. The objective to this project is to study the school assessment system for primary school. Second, to develop the Online School Assessment System for primary school. Lastly, to test the functionality of Online School Assessment System. In this project, the methodology that was used is Waterfall Methodology. There is five phase in Waterfall methodology that is the planning phase, the second is the analysis where the information was gathers, the third is designing the interface of the website, the fourth is the implementation where the code will be implement to the website and the last phase is the testing. The testing were conducted to ensure all the function work according to the requirement without any error. It also to ensure that the system have achieve the objective and can solve the problem that happen before.